Oracle v. Google: A High-Stakes Legal Fight for the Software Industry. - Sprigman, Christopher Jon (Communications of the ACM, 2015)
The article discusses the U.S. court case Oracle v. Google, which may be heard by the U.S. Supreme Court and which concerns the copyright status of software application programming interfaces (APIs). The author argues that the Supreme Court should hear the case and should overturn a ruling by the U.S. Court of Appeals for the Federal Circuit that software APIs are copyrightable. Details on Google's use of the Java programming language are presented.